Hsa_circ_0072732 enhances sunitinib resistance of renal cell carcinoma by inhibiting ferroptosis - Xiaorui Tian; Jun Liu; Cheng Yi; Xiangyun You; Chunli Yuan (Discover Oncology)
Abstract Background Renal cell carcinoma (RCC) is one of the most diagnosed urological malignancies with high mortality and increasing incidence. What’s more, the sunitinib resistance undoubtedly increased the difficulties in RCC therapy. Circular RNAs (circRNAs) are a newly found type of non-coding RNAs with a special circular structure, and are found to participate in the occurrence development, chemoresistance, and prognosis of cancers. Ferroptosis regulates disease progression mainly via polyunsaturated fatty acid metabolism and glutamine catabolic pathways. The mechanism of circRNAs contributed to sunitinib resistance through ferroptosis has not been elucidated clearly. Materials and methods In our research, we identified a novel circRNA Hsa_circ_0072732 from circRNA datasets (GSE108735 and GSE100186). RNase R and Actinomycin D assays were used to detect the loop structure and stability of circRNAs. qRT-PCR and western blot were used for the detection of RNA and protein levels. CCK8 assays were used to detect proliferation and cell viability. Lipid peroxidation (MDA), and reactive oxygen species (ROS) were detected by indicted kits. Dual-luciferase reporter and RNA pull-down assays were used to detect the RNA interactions. Results Our results showed that Hsa_circ_0072732 was highly expressed in RCC cells. Further investigations showed that the silence of Hsa_circ_0072732 could increase RCC sensitivity to sunitinib. Hsa_circ_0072732 contributed to sunitinib chemoresistance by impairing ferroptosis. Hsa_circ_0072732 exerts its function mainly by acting as sponges for miR-548b-3p and regulating the expression SLC7A11. Our research suggests that ferroptosis is involved in sunitinib resistance, and targeting ferroptosis is a promising way for RCC treatment. Conclusion Our research suggests Hsa_circ_0072732 enhanced renal cell carcinoma sunitinib resistance by inhibiting ferroptosis through miR-548b-3p/SLC7A11.